Perizinan Perusahaan Jasa Angkutan Laut dalam Melakukan Freight Forwarding (Ekspedisi) Berdasarkan Undang – Undang Nomor 17 Tahun 2008 Tentang Pelayaran (Studi Kota Pontianak) - Ahyana Syahila Sukmana (Jurnal Hukum dan Sosial Politik, 2025)
SIUPAL is a Sea Transportation Company Business License which is a permit that will later be given to shipping companies. The goal is to provide comfort in doing business, because basically all business activities, both small and large scale, must have a company permit in order to operate properly in accordance with applicable regulations and can also reduce unwanted things. A national sea transportation company is a sea transportation company that is established based on Indonesian law that can carry out sea transportation activities in waters and from and to foreign ports. The obstacles faced include untimely completion of permits, lack of employee availability, complexity in submitting online permits, and lack of security or back up for front office employees. Efforts made by using service quality strategies and human resource improvement strategies.